Comparative analysis of Propp’s perspective with Greimas and Bermond about narration from Structuralism viewpoint - Reza Ghanbari Abdolmaleki; Ailin Firoozian Pouresfahani (مطالعات زبانی و بلاغی)
The investigation of basic narrative structures which were followed regularly between formalists and structuralists in twentieth century, has a salient role in literary researches. Among formalists, Vladimir Propp’s theory, manifested in the book “Morphology of Folktale”, can be mentioned as the first attempt in theorizing narration that later attracted French narrative structuralists' attention. By utilization of Propp method, it was revealed that final narrative structure could be determined. This method in which the functions of narrative design were taken into consideration, was changed in Greimas’s and Bremond’s works. By studying structural semantics and continuing Propp’s researches, Greimas could present actantial model. Also Bremond whose works were based on Propp’s view, completed and revised his opinion according to Propp’s theory. In the present study, by using descriptive-analytical method, Greimas’s and Bremond’s narrative viewpoints will be compared with Propp’s opinion. Then it will be represented how Greimas and Bremond, applied Propp’s perspective as a source for reflecting their comprehensive theories.